Are dopaminergic genotypes risk factors for eating behavior and obesity in adults?. (27th July 2017) - Avsar, Orcun; Kuskucu, Aysegul; Sancak, Seda; Genc, Ece
Highlights: Obesity is becoming a serious health problem worldwide among individuals of all ages. This study reported significant cues for the relationship between obesity and gene polymorphisms of dopamine metabolizing enzymes. Our previous data suggested that DAT1 SNP (rs27072) might be a risk factor for the development of adult obesity. 'Eating for reward' might be related with obesity to compensate for modified dopamine neurotransmission. COMT Val/Met (rs4680) genotype was found to be protective for adult obesity. Abstract: Dopamine (DA) is the main modulator of the brain reward system and significantly regulates food intake. The idea that obesity is a neurobiological disease rather than a metabolic disorder, is the basis of the study. Changes in dopamine neurotransmission affect the brain reward system in a direct way. Furthermore, changes in the reward system influence the eating behavior in human. The enzymes monoamine oxidase A (MAOA) and catechol-O-methyltransferase (COMT) terminate the DA function by metabolizing it. In our study, the control group which included 214 individuals and 234 subjects with obesity were investigated for MAOA-u VNTR and COMT (rs4680) polymorphisms. In our study, statistical analysis has showed that in control group Val/Met COMT genotype was significantly higher compared with the patient group ( p = 0.04). When the groups were compared in terms of eating behavior, the number of the subjects who ate for reward was significantly higher in patient group ( p = 0.03). Our findings demonstrated that eating behavior might have an effect on obesity and dopaminergic polymorphisms could be risk factors for the development of obesity in Turkish population.